2009
DOI: 10.1080/09603100903266807
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and corporate financing

Abstract: This article examines empirically the effect of ownership structure on the corporate financing decision from the agency theory perspective. This article contributes to the literature by examining the static and the dynamic effects of managerial insiders and large shareholders' ownership on the capital structure. Based on panel data analysis for a sample of Jordanian industrial firms during the period 2001 to 2005, the study provides empirical evidence indicating that the debt ratio is negatively related to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
31
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
8
31
2
1
Order By: Relevance
“…With the purpose to empirical analyze the defined hypotheses, a sample of 418 Italian USOs has been investigated during an exploration period of five years (from 2010 to 2014). The findings show that, in line with the evidence of Al-Fayoumi and Abuzayed (2009), managerial ownership is negatively associated with the USO's leverage. This means that manager that are also shareholders of USOs are more apt to decrease the level of firm's debt in order to reduce the risk of bankruptcy.…”
Section: Results Discussion and Conclusionsupporting
confidence: 76%
See 1 more Smart Citation
“…With the purpose to empirical analyze the defined hypotheses, a sample of 418 Italian USOs has been investigated during an exploration period of five years (from 2010 to 2014). The findings show that, in line with the evidence of Al-Fayoumi and Abuzayed (2009), managerial ownership is negatively associated with the USO's leverage. This means that manager that are also shareholders of USOs are more apt to decrease the level of firm's debt in order to reduce the risk of bankruptcy.…”
Section: Results Discussion and Conclusionsupporting
confidence: 76%
“…This might reduce the positive impact of the agency-related benefits in view of the rise of company debt, generating a non-linear inverted U-shaped association among managerial ownership and debt (Short and Keasey, 1999;Margaritis and Psillaki, 2010). Also, further studies (Berger et al, 1997;Al-Fayoumi and Abuzayed, 2009) highlight how owner managers tend to decrease corporates' debt as of the additional bankruptcy risk.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…They observed that firm growth and profitability had a negative relationship with leverage, while the size of a firm was positively related to leverage. Al-Fayoumi and Abuzayed (2009) studied the capital structure of firms in Jordan and found that variables such as profitability, firm size and growth opportunities had a significant impact on capital structure (results that are consistent with theory predictions). On the other hand, tangibility of assets, risk and being a non-debt tax shield had no significant impact.…”
Section: Background and Hypothesis Developmentsupporting
confidence: 56%
“…We have used return on assets (ROA) as a measure of firm profitability. It has been used in various studies including Shah & Jam-e-Kausar[29],Rajan and Zingales[16], Al-Fayoumi[36].Hypothesis 5-firm value and profitability have a significant positive relation. 6) Growth-as per pecking theory and trade off theory there exists a positive and negative relation between firm leverage and growth as shown by Myres[10],…”
mentioning
confidence: 99%